Pemilihan Akun Media Sosial INSTAGRAM oleh HOLIDAY INN Bandung - Satyadewi, Ajeng Jayanti; Hafiar, Hanny; Nugraha, Aat Ruchiat (Jurnal The Messenger, 2017)
The development of information technology in the hospitality institute is very important to be adopted in order to improve the quality of service to prospective customers.   The purpose of this study was to determine the communication planning, through the process of share, optimize, manage, and engage in @holidayinnbandung Instagram. The research method is descriptive qualitative research methods and the foundation of the concept is The Circular Model of SOME. The results showed, the planning of communication via Instagram @holidayinnbandung is quite optimal, sharing process of Instagram selection motivated by the successful use of hash tags by international IHG. Optimizing the planning process starting from the promo to be made by optimizing the content is done by looking at the aspects of a photo and caption. Engagement process planning is done using the brand influencers and create content that is attractive to be able to entertain and interact with the followers.